2020
DOI: 10.1016/j.celrep.2020.108256
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Interaction between Vascular Filopodia and Neural Stem Cells Shapes Neurogenesis in the Ventral Telencephalon

Abstract: Highlights d Nascent vessels extend filopodia toward the ventricle in the embryonic brain d Vascular filopodia contact apical progenitors in mouse and human ventricular zone d High filopodia density prolongs neural progenitor mitosis and favors neuronal differentiation d Mitotic apical progenitors induce vascular filopodia growth by VEGF-A upregulation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 57 publications
1
35
0
Order By: Relevance
“…At this time point, we noticed that endocardial protrusions can be detected in close proximity to trabecular CMs (Figure 1D’’ and D’’’, Figure 1-video 3). Recently, it has been shown that endothelial protrusions modulate neurogenesis by affecting progenitor proliferation in the developing brain (Di Marco et al, 2020). To determine whether endocardial protrusions affect CM proliferation, we performed EdU labeling between 28 and 72 hpf and analyzed the heart at 72 hpf.…”
Section: Resultsmentioning
confidence: 99%
“…At this time point, we noticed that endocardial protrusions can be detected in close proximity to trabecular CMs (Figure 1D’’ and D’’’, Figure 1-video 3). Recently, it has been shown that endothelial protrusions modulate neurogenesis by affecting progenitor proliferation in the developing brain (Di Marco et al, 2020). To determine whether endocardial protrusions affect CM proliferation, we performed EdU labeling between 28 and 72 hpf and analyzed the heart at 72 hpf.…”
Section: Resultsmentioning
confidence: 99%
“…Neurogenesis and angiogenesis are two different processes that seem to be tightly coupled during embryonic neural development. Nascent blood vessels were reported to actively contact dividing neural stem cells and have a function in their behavior, impacting proper brain development (Di Marco et al, 2020). To further understand how culturing cerebellar organoids in dynamic conditions impacts on angiogenic transcriptional profiles, we analyzed the number of normalized read counts of representative genes annotated in the sprouting angiogenesis process (GO:0002040).…”
Section: Transcriptional Modulation Of Genes Involved In Angiogenic Processes By Dynamic Conditionmentioning
confidence: 99%
“…The vWF-A domain 1 directly binds to angiogenesis-inducing factors such as vascular endothelial growth factor-A (VEGF-A) and platelet-derived growth factor-BB (PDGF-BB). VEGF and PDGF-BB play an important role in vascularization [23] and neurogenesis, respectively, during early development [24].…”
Section: Possible Roles Of the Vwf-a And Lccl Domains In Akhmentioning
confidence: 99%
“…Although the interaction of blood vessels with NSCs in the adult brain niche has already been widely reported [25][26][27], recent reports have shown that the timing of differentiation of NSCs/NPCs into neurons is implicated in the interaction between embryonic vascularization and neurogenesis. For instance, Di Marco et al showed that nascent periventricular vessels interact with dividing apical neural progenitors by using vascular filopodia induced by the upregulation of VEGF-A in a cell-cycle-dependent manner [23]. They concluded that vascular filopodia helps in fine-tuning NSC behavior for proper brain development.…”
Section: Possible Roles Of the Vwf-a And Lccl Domains In Akhmentioning
confidence: 99%